A Transcriptomic Approach Provides Insights on the Mycorrhizal Symbiosis of the Mediterranean Orchid Limodorum abortivum in Nature - Rafael B. S. Valadares; Fabio Marroni; Fabiano Sillo; Renato R. M. Oliveira; Raffaella Balestrini; Silvia Perotto (Plants, 2021)
The study of orchid mycorrhizal interactions is particularly complex because of the peculiar life cycle of these plants and their diverse trophic strategies. Here, transcriptomics has been applied to investigate gene expression in the mycorrhizal roots of Limodorum abortivum, a terrestrial mixotrophic orchid that associates with ectomycorrhizal fungi in the genus Russula. Our results provide new insights into the mechanisms underlying plant–fungus interactions in adult orchids in nature and in particular into the plant responses to the mycorrhizal symbiont(s) in the roots of mixotrophic orchids. Our results indicate that amino acids may represent the main nitrogen source in mycorrhizal roots of L. abortivum, as already suggested for orchid protocorms and other orchid species. The upregulation, in mycorrhizal L. abortivum roots, of some symbiotic molecular marker genes identified in mycorrhizal roots from other orchids as well as in arbuscular mycorrhiza, may mirror a common core of plant genes involved in endomycorrhizal symbioses. Further efforts will be required to understand whether the specificities of orchid mycorrhiza depend on fine-tuned regulation of these common components, or whether specific additional genes are involved.